Features of the manifestation of strength and speed-strength abilities of elite armwrestlers of different weight categories - Oleg Kamayev; Victor Dzhym; Andrii Zabora; Marina Dzhym; Liudmyla Kanunova; Oleksandr Piven (Kharkiv State Academy of Physical Culture, 2024)
Purpose. To determine the features of the manifestation of strength and speed-strength indicators in the components of the competitive exercise of leading armwrestlers of different weight categories. Material and Methods. The study involved 3 of the best armwrestlers in the world in different weight categories: athlete 1 (weight 62 kg; age 39 years) - multiple world champion (Ukraine), athlete 2 (weight 90 kg, age 36 years) - multiple world champion (Ukraine) , athlete 3 (weight 136 kg, age 34 years) - multiple world champion (Ukraine). The strength characteristics of athletes were determined in four test exercises that ensure the performance of a competitive action in armwrestling: flexion of the fingers, stretch with a hammer, hook and bending the hand. These exercises were performed with the left and right hands. Strength indicators in all test exercises were measured with an FL1K 0.5N, 1000N electric strain gauge dynamometer, Kern & Sohn GmbH (China) with an accuracy class of up to 50 g, fixed on a specialized armwrestling table using a specially made an author's block device. In the course of statistical analysis, the following parameters were determined and calculated: maximum (F) and relative (F1 = ƩF / m) strength, kg; total strength index in four strength exercises (ƩF = F1 + F2 + F3 + F4), kg; time to reach maximum strength (Ʃt = t1 + t2 + t3 + t4), s; speed-strength index (J = ƩF / Ʃt), kg*ms-1; average strength, index of four exercises ( = ƩF / 4), kg; total strength gradient of four exercises (Ʃt0,5F), ms; speed-strength index in the first 500 ms (J500 = ƩF500 / Ʃt500), kg*ms-1; time to reach 1 kg force (t1 = Ʃt0.5F / (0.5×F)), ms*kg-1. Results. Athlete 1, weighing 62 kg, reached the maximum value of the strength of the left arm, equal to 181.8 kg, in 4.8 s, and in the right - after 4.4 s and reached 170.0 kg. The speed-force index when reaching maximum strength was, respectively, 0.038 kg*ms-1 and 0.039 kg*ms-1. For athlete 2, weighing 90 kg, the maximum strength values were determined after 5.3 s with the left hand and after 5.5 s with the right hand and, respectively, amounted to 233.8 kg and 260.5 kg. At the same time, the speed-strength index reached 0.044 kg*ms-1 with the left hand, and 0.047 kg*ms-1 with the right hand. The achievements of the maximum strength value of the heaviest athlete 3, weighing 136 kg, of both left and right arms were significantly better and reached 248.1 kg and 275.4 kg, respectively. At the same time, the time characteristics for reaching the limiting force values are relatively low and amounted to 4.9 s and 5.1 s. In this regard, noticeably high speed-strength index values are observed: left arm - 0.051 kg*ms-1; right - 0.054 kg*ms-1. Conclusions. The study made it possible to establish that the heaviest athlete 3 has the highest overall maximum strength, but in the test exercises, which are elements of performing competitive hook and hammer pull movements, the lighter athlete 2 demonstrated a higher result. The lightest athlete 1, whose weight is 62 kg, has a high result in the relative strength indicator. The heaviest athlete 3 has significantly higher levels of explosive, fast, slow and maximum strength and, as a result, a higher speed-strength index, due to which he wins quick victories in competitions. Athletes 1 and 2, who have lower body weight, according to such time characteristics as force gradient, time to reach 1 kg of force, speed-strength indicator at the last second, have respectively better results. This indicates that athletes 1 and 2 achieve their victories in competitions due to these very characteristics.